Agromarketing as an instrument of managing the competitiveness of agricultural sector (Journal of Economic Research & Business Administration, 2016)
Today there is no industrially developed country where marketing activity to some extent wouldn’t practice. The present stage of development of agroindustrial complex is characterized by creation of essentially new conditionsfor business activity. First, it is about strengthening of the competition both on internal and on external the food markets. The main competitors in these markets are the countries with the developed agrarian sector of economy allocating huge amounts of money for subsidizing of agriculture. The economic situation when market orientation of agrarian production is staticized is formed. In this situation into the forefront the marketing allowing to consider as much as possible market condition changes, market behavior of consumers of agricultural products, segmentation of the consumer and raw markets and other factors acts. The analysis of current situation in the market of agricultural production of the Republic of Kazakhstan showed that agromarketing as system didn’t gain distribution in formation of agriculture yet. In this regard in this article the essence and features of agrarian marketing reveal, agro-industrial activity of the Republic of Kazakhstan is analysed, the main reasons constraining development of agromarketing in Kazakhstan are established.
Keywords: marketing; agromarketing; agro-industrial complex; agriculture; market